How Effective Is Toothbrush Education through Environmental Changes in Elementary School Children - Dyah Nawang Palupi Pratamawari; Grandyna Ansya Balgies; Yvonne A.B. Buunk-Werkhoven (The Korean Society of Dental Hygiene Science, 2022)
Background: Nowadays, dental health problems in Indonesia are still quite high. It is one of which influenced by low public awareness of the importance of maintaining the health of teeth and mouth that can be measured by toothbrushing behavior. Based on the results of RISKESDAS 2018, only 2.8 percent of the population has a proper toothbrushing behavior. Behavior tends to form at age 6 to 12 years. At this age, children begin to develop habits that tend to settle until adulthood, including toothbrushing behavior. Social cognitive theory is a theory of behavioral change that explains that behavioral changes are influenced by the environment, personal, behavior where these three factors influence each other. This study aims to identify changes in the dental behavior of second grades students before and after the joint toothbrushing at school for 21 days.Methods: A pre-experimental study-design was conducted on elementary school by pre-post treatment method where there are 2 classes that get intervention and 2 other classes as control. A joint toothbrush is performed every morning before the school activities begin. Before and after the joint toothbrushing, all classes are given questionnaires to see if there are any changes in behavior seen through knowledge, attitudes, and practice.Results: Respondent group showed increasement on their knowledge, attitudes, and behaviors towards toothbrushing. In contrast, the control groups showed no significant differences in the 3 factors.Conclusion: In this study the education of toothbrushing through environmental changes is quite effective in elementary school children. Insights into the benefits of this program and refinements of optimally targeted intervention, including longitudinal studies are needed to improve the results.